A symbiotic nondipolar droplet supersolid in a binary dipolar–nondipolar Dy-Rb mixture - Adhikari, S.K. [UNESP] (Elsevier, 2024)
We demonstrate the formation of two types of symbiotic nondipolar droplet supersolid in a binary dipolar–nondipolar mixture with an interspecies attraction, where the dipolar (nondipolar) atoms are trapped (untrapped). In the absence of an interspecies attraction, in the first type, a dipolar droplet supersolid exists, whereas in the second type, there are no droplets in the dipolar component. To illustrate, we consider a 164Dy-87Rb mixture, where the untrapped 87Rb supersolid sticks to the trapped 164Dy supersolid due to the interspecies attraction and forms a symbiotic supersolid with overlapping droplets. The first (second) type of symbiotic supersolid emerges for the scattering length a 1 = 85 a 0 ( a 1 = 95 a 0 ) of 164Dy atom, while under an appropriate trap a dipolar droplet supersolid exists (does not exist) for no interspecies interaction, where a 0 the Bohr radius. This study is based on the numerical solution of an improved binary mean-field model, where we introduce an intraspecies Lee–Huang–Yang interaction in the dipolar component, which stops a dipolar collapse and forms a dipolar supersolid. To observe this symbiotic droplet supersolid, one should prepare the corresponding fully trapped dipolar–nondipolar supersolid and then remove the trap on the nondipolar atoms.